2009
DOI: 10.4049/jimmunol.0900861
|View full text |Cite
|
Sign up to set email alerts
|

Direct Antigen Presentation and Gap Junction Mediated Cross-Presentation during Apoptosis

Abstract: MHC class I molecules present peptides from endogenous proteins. Ags can also be presented when derived from extracellular sources in the form of apoptotic bodies. Cross-presentation of such Ags by dendritic cells is required for proper CTL responses. The fate of Ags in cells initiated for apoptosis is unclear as is the mechanism of apoptosis-derived Ag transfer into dendritic cells. Here we show that novel Ags can be generated by caspases and be presented by MHC class I molecules of apoptotic cells. Since gap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
45
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 40 publications
4
45
0
1
Order By: Relevance
“…Surprisingly, DCs cultured with live tumor cells induced complete tumor protection, whereas DCs cultured with apoptotic tumor cells induced protection but not in all mice ( Figure 7A). This result coincided with the IFN-␥ response, that is, DCs cultured with live tumor cells induced better IFN-␥ responses to B16 cells ( Figure 7B) or to gp100 [25][26][27][28][29][30][31][32][33] or TRP2 181-188 tumor CD8 epitopes (supplemental Figure 4C) than DCs cultured with apoptotic cells. These responses were essentially the result of CD8 ϩ T cells, as shown by intracellular IFN-␥ labeling ( Figure 7C), but CD4 ϩ T cells also produced IFN-␥ albeit at a lower rate ( Figure 7D).…”
Section: Protection From Tumoral Challenge In Vivo After Injection Wisupporting
confidence: 65%
See 2 more Smart Citations
“…Surprisingly, DCs cultured with live tumor cells induced complete tumor protection, whereas DCs cultured with apoptotic tumor cells induced protection but not in all mice ( Figure 7A). This result coincided with the IFN-␥ response, that is, DCs cultured with live tumor cells induced better IFN-␥ responses to B16 cells ( Figure 7B) or to gp100 [25][26][27][28][29][30][31][32][33] or TRP2 181-188 tumor CD8 epitopes (supplemental Figure 4C) than DCs cultured with apoptotic cells. These responses were essentially the result of CD8 ϩ T cells, as shown by intracellular IFN-␥ labeling ( Figure 7C), but CD4 ϩ T cells also produced IFN-␥ albeit at a lower rate ( Figure 7D).…”
Section: Protection From Tumoral Challenge In Vivo After Injection Wisupporting
confidence: 65%
“…DCs were cultured for 16 hours in the presence of LPS, either alone or with B16 MHC class I-restricted epitopes (gp100 [25][26][27][28][29][30][31][32][33] , 10M each), or with live B16 cells in the presence of z-VAD, or with apoptotic B16 cells. DCs were then washed, purified, ␥-irradiated (100 Gy) to eliminate any residual live tumor cells, and immediately injected intravenously into C57Bl/6 mice on day 0 (5 ϫ 10 5 ) and 14 (3 ϫ 10 5 ).…”
Section: Protection From Tumoral Challenge In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, almost one-third of the mapped peptides contained one or more cleavage sites that were not derived from classical endosomal processing. Apoptotic cells are present in the lymph as byproducts of cellular turnover of different parenchymal organs, and caspase-processed peptides likely derive from these cells (52). Other peptides contained at least one matrix metalloprotease or calpain cleavage site, indicating their potential source from extracellular matrix remodeling processes.…”
Section: Peptide Sourcementioning
confidence: 99%
“…Recently, it has been shown that cDC can also capture peripheral antigens not only as proteins but also as preprocessed peptides found in biological fluids or delivered in the plasma, subcutaneously or in the peritoneal cavity, which directly drains in the peritoneal lymphatics (32,33,35,50,51). Antigens acquired through conventional phagocytosis or autophagy generate an MHC II peptidome processed mostly by endosomal cathepsins, whereas peptides found in biological fluids could derive from a greater variety of processing pathways (15,27,28,52). Thus, in theory, the richness of naturally processed peptides found in biological fluids, including the lymph, could greatly expand the MHC II-presented self-peptidome.…”
mentioning
confidence: 99%